COMPETITIVENESS ANALYSIS AND FACTORS THAT AFFECTING INDONESIA’S EXPORT OF MANGOSTEEN IN THE INTERNATIONAL MARKET - Ningrum, Hanifah; Kusnaman, Djeimy; Situmorang, Sawitania (Journal of Agri Socio Economics and Business, 2024)
Tropical fruits are one of Indonesia's leading horticultural products, where mangosteen fruit contributes the largest export to Indonesia's total fruit exports. However, Indonesia's mangosteen export share is still very low and this should be maximized. This study aims to analyze the competitiveness of Indonesian mangosteen exports in the international market and compare with other mangosteen exporting countries in the international market and find out the factors that affect the competitiveness. The data used is in the form of secondary data from 2003 to 2022. The analysis methods used are ECI, ISP and multiple regression analysis. The results of the ECI analysis show that Indonesian mangosteen has a competitive advantage and experiences an increasing export trend with a value of 1.217 and ISP shows that Indonesia tends to be a mangosteen exporting country and is at the maturity stage with a value of 0.903. However, Indonesia's competitive position is still below other countries such as Thailand, India, Peru and Kenya. Factors that affect Indonesia's ECI significantly are export volume of Thailand’s mangosteens and harvest area of Indonesia’s mangosteens.